2019
DOI: 10.12973/eu-jer.8.4.1175
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Assessment and Cross-Cultural Adaptation of the Grit-S Scale among Omani and American Universities’ Students

Abstract: The current study aimed to adopt and assess the psychometric properties and measurement invariance of Grit-S among Omani and American students (N = 487) using Exploratory Factor Analysis (EFA) and Multi-Group Confirmatory Factor Analysis (CFA). The scale's construct validity was estimated by investigating its associations with achievement goal orientations (AGOs). EFA results suggested that a two-factor solution (i.e., perseverance of effort [G_PE] and consistency of interest [G_CI]) was the best factorial str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Meaning, gritty students show more diligence in surmounting barriers and lasting interest to fulfill their goals despite setbacks and lack of assistance. More recent empirical research has highlighted that grit is positively associated with numerous academic outcomes, including academic performance through numerous mediators (e.g., self-efficacy and achievement orientation goals; 3; 18), Mastery and performance-approach goals [ 2 ], intellectual engagement [ 31 ], metacognition [ 32 ], life satisfaction [ 33 ], and graduation rate [ 34 ]. A recent meta-analysis study revealed that grit correlated with undergraduate GPA, retention, intent to persist in college, college satisfaction, and self-efficacy [ 35 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Meaning, gritty students show more diligence in surmounting barriers and lasting interest to fulfill their goals despite setbacks and lack of assistance. More recent empirical research has highlighted that grit is positively associated with numerous academic outcomes, including academic performance through numerous mediators (e.g., self-efficacy and achievement orientation goals; 3; 18), Mastery and performance-approach goals [ 2 ], intellectual engagement [ 31 ], metacognition [ 32 ], life satisfaction [ 33 ], and graduation rate [ 34 ]. A recent meta-analysis study revealed that grit correlated with undergraduate GPA, retention, intent to persist in college, college satisfaction, and self-efficacy [ 35 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In detail, Hong et al [ 6 ] showed four profiles of undergraduates based on four outcomes of academic motivation (i.e., self-efficacy, achievement goals, value, and cost). These profiles were [ 1 ] High cost (i.e., was characterized by high cost and low self-efficacy, goals, and values; 9.1%), [ 2 ] Moderately motivated (i.e., had students with an average level of all motivation; 37.7%), [ 3 ] High goals (i.e., contained students with higher achievement goals compared to other profiles; 41.9%), and [ 8 ] Mastery-driven (i.e., had students with low-performance achievement goals and avoidance goals; 11.3%).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations